Pendampingan Tracer Study: Pembuatan Website dan Pengolahan Data - Aswi; Poerwanto, Bobby; Mar’ah, Zakiyah (Insan Kreasi Media, 2023)
Tracer study and user survey are two instruments used to obtain data related to alumni when they are graduated, during the transition period, and the time when tracking is filled. The data is not only to get an overview of the condition of alumni and response from their supervisor, it is also used to provide data on accreditation needs at both BAN PT and LAMs. This activity aims to maximize the implementation of tracer studies based on criteria from BAN PT, and also provide a tracer study website to facilitate data processing. To solve this problem, there were 2 main activities carried out, namely assistance in making a tracer study website which was carried out for 1 month, and training in analyzing data. The first result of this activity was the availability of a website tracer study which has accommodated partner’s tracer study needs, and increased knowledge related to tracer study implementation standards to maximize value in study program accreditation. Secondly, A tracer study website has been created and can help provide supporting data and analysis of tracer study data.